2015
DOI: 10.1039/c4fd00179f
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved in situ X-ray diffraction study of crystallisation processes of large pore nanoporous aluminophosphate materials

Abstract: Time resolved high-resolution X-ray powder diffraction was utilized to obtain detailed changes in the crystal structure parameters during the hydrothermal crystallization process of the nanoporous aluminophosphate AlPO-5 (AFI) structure. This in situ study offered not only the influence of metal ions on the onset of crystallization and estimation of the activation energy of the process, but also allowed us to determine in detail the changes in lattice parameters during this process. More importantly the time-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some of the reasons are that they may not be ordered and also that in the majority of the cases, the concentration of the metal ions is too small to show any effect. However, Simmance et al [99,100] indeed show that there are specific lattice expansions in certain directions, in cobalt and zinc substituted aluminophosphates. Despite this observation, it is difficult to determine the local structure of the substituted metal ions unless a more specific local structural tool is used, specifically adaptable to systems with low concentrations of heteroatoms.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Some of the reasons are that they may not be ordered and also that in the majority of the cases, the concentration of the metal ions is too small to show any effect. However, Simmance et al [99,100] indeed show that there are specific lattice expansions in certain directions, in cobalt and zinc substituted aluminophosphates. Despite this observation, it is difficult to determine the local structure of the substituted metal ions unless a more specific local structural tool is used, specifically adaptable to systems with low concentrations of heteroatoms.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Recently, a time-resolved in situ energy dispersive X-ray diffraction (EDXRD) experiment was developed using a synchrotron X-ray device. 26,[74][75][76] This is a very useful tool for investigating the intercalation mechanism and its kinetics, since the intercalation reactions can be simultaneously traced as soon as the guest species is added to the host suspension. From this time-resolved in situ EDXRD, Taviot-Gueho et al clarified the second-stage phenomena (the interstratified structure) during the intercalation of tartrate into Zn 2 Cr-Cl LDH.…”
Section: Examples Of 1-d Electron Density Mapping Formentioning
confidence: 99%
“…7 -substituted aluminophosphates. 41 Compared to un-substituted AlPO 4 -5, 13.716 A, the greater a (¼b) parameters indicated that the metal ions was part of the framework, which could result in the lattice expansion. Furthermore, the lattice expansion was limited, which might relate to the amount of Cr 3+ interacted with the framework was limited.…”
Section: -56mentioning
confidence: 99%
“…The increase in c parameter during the crystallization process could be ascribed to the uptake of water molecular and the template orientation, as explained by Sankar. 41 The increase in the c parameter, over the crystallization time, was due to the uptake of water molecules which may coordinate to Al 3+ ions accessible in the channel direction, 59 ) should therefore show a larger increase in the c parameter compared to MeAPO-5. On the other hand the template orientation within the structure could also play a role in this change in c parameter and cell volume.…”
Section: -56mentioning
confidence: 99%
See 1 more Smart Citation